Ovarian Sclerosing Stromal Tumour Associated with Hirsutism in an Adolescent - Mehmet Dolanbay; Mehmet Serdar Kütük; Semih Uludağ; Mahmut Tuncay Özgün; Hülya Akgün; Bülent Özçelik (Gynecology Obstetrics & Reproductive Medicine, 2014)
Sclerosing stromal tumours are rare ovarian neoplasm in adolescent girls. Herein, we describe a case of 17 year-old adolescent girl presented with hirsutism and abdomino-pelvic palpable mass. Ferriman Gallwey score was 9 and abdominal examination revealed a pelvic mass in 150 mm in diameter. At laparatomy there was minimal free fluid in the pelvis and yellow to pink in colour pelvic mass in right ovary. Unilateral salpingo-oophorectomy was done. Histological examination reported as benign sclerosing stromal tumour of the right ovary. In adolescent patients sclerosing stromal tumours of ovary may be presented with hirsutism and abdomino-pelvic mass. Attentive pelvic examination and imaging is important in hirsute adolescent patients.